A Systematic Literature Review of Physical Activity-Based Health Programs for Indigenous Women: Impacts on Physical Activity Levels, Obesity, and Community Building. (June 2021) - Wicklum, Sonja; Willis, Elsy; Amson, Ashley; McGuire, K. Ashlee; Crowshoe, Lynden Lindsay; McBrien, Kerry; Henderson, Rita
Indigenous women experience a disproportionate burden of chronic diseases and health challenges related to obesity. The need for culturally relevant programming to support and empower women to optimize health is well established. Participatory physical activity [PA]-focused programming responsive to the sociocultural realities of Indigenous women may hold promise. However, obesity and chronic disease literature for Indigenous women focusing on PA change predominantly discusses individual behaviors, leaving a knowledge gap around the social and environmental supports needed to realize improved outcomes. We searched PubMed, Ovid MEDLINE, CINAHL, Bibliography of Native North Americans, and the University of New Mexico's Native Health Databases for English language peer-reviewed articles on PA-based programs addressing prevention or management of obesity with Indigenous women as a primary focus. Fifteen articles, representing 13 unique programs, were included in the review. Outcome measures included program attendance and factors influencing program acceptance, PA, biochemical markers and blood pressure, weight and waist circumference measurements, the development of social supports, and nutritional knowledge acquisition. Although some studies found improvements in PA level and other outcomes, the marked variability in study design makes it difficult to draw conclusions about best practices for PA-based wellness and weight management programs for Indigenous women. However, programming that acknowledges and provides accommodation for the complex factors that influence behavior, incorporates cultural and community elements, and integrates opportunities for supportive network development may improve outcomes.